2018
DOI: 10.2807/1560-7917.es.2018.23.47.1700423
|View full text |Cite
|
Sign up to set email alerts
|

Acute flaccid paralysis (AFP) surveillance: challenges and opportunities from 18 years’ experience, Spain, 1998 to 2015

Abstract: Acute flaccid paralysis (AFP) surveillance is key for global polio eradication. It allows detecting poliovirus (PV) reintroductions from endemic countries. This study describes AFP surveillance in Spain from 1998 to 2015. During this time, 678 AFP cases were reported to the Spanish National Surveillance Network. The mean notification rate was 0.58 AFP cases/100,000 population under 15 years old (range: 0.45/100,000–0.78/100,000). Two periods (P) are described: P1 (1998–2006) with the AFP notification rate rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
7
16
0
Order By: Relevance
“…It is therefore unlikely to have missed cVDPV or WPV circulation in the ESA sub-region countries and can confidently support the certification of the WHO/AFRO region. The study found out the most the reported AFP cases for the period age group was 0 - 3 years which resembles the results from a study in Spain where the majority of cases 310 (45.7%) were under-fives and in Southern China where 75% of patients with AFP were of 0-3 years [ 24 , 25 ]. The paralysis of the lower-limbs was reported in 84% of the reported AFP cases for the period from 2012 to 2019, this is similar to what was reported in Southern China where 70% of the reported AFP cases had lower-limbs paralysis [ 25 ].…”
Section: Discussionsupporting
confidence: 81%
“…It is therefore unlikely to have missed cVDPV or WPV circulation in the ESA sub-region countries and can confidently support the certification of the WHO/AFRO region. The study found out the most the reported AFP cases for the period age group was 0 - 3 years which resembles the results from a study in Spain where the majority of cases 310 (45.7%) were under-fives and in Southern China where 75% of patients with AFP were of 0-3 years [ 24 , 25 ]. The paralysis of the lower-limbs was reported in 84% of the reported AFP cases for the period from 2012 to 2019, this is similar to what was reported in Southern China where 70% of the reported AFP cases had lower-limbs paralysis [ 25 ].…”
Section: Discussionsupporting
confidence: 81%
“…However, it was only implicated in 6.8% of AFP cases. Recent AFP surveillance reports from China, Spain, and West Africa agree with these previous findings, with 100%, 81% and 90% of positive EV samples from AFP patients belonging to the EV-B species, respectively [55][56][57][58].…”
Section: Enterovirus Bsupporting
confidence: 80%
“…In addition, a potential role for virus-induced immune responses in neuropathology needs to be explored. While nearly every EV type has been identified in surveillance or case reports from AFP patients [17,56,57,[160][161][162][163][164][165][166], EV-B-associated AFP deserves more attention. Because EV-B is such a diverse species and the frequency of outbreaks can have long cyclical patterns, it has been difficult to associate any specific EV-B type as a frequent cause of AFP.…”
Section: Conclusion/perspectivementioning
confidence: 99%
“…Polio-associated AFP is a rare disease overall, and its declining incidence and lack of perceived importance has led to difficulties in use and verification of individual cases [3]. As discussed in this week’s Eurosurveillance report of the Spanish experience of AFP surveillance over the past 20 years, in at least a third to two thirds of cases the supporting virological investigations may also be less than optimum [9]. The findings emphasise that the overall sensitivity of passive AFP case finding, as a tool for detection of polio circulation in the era of eradication, is insufficient and needs to be supplemented.…”
Section: Clinical Surveillancementioning
confidence: 99%